Effect of soil saturation and grain size on coupled hydrothermal flow in fine sands based on X-ray μCT imaging. (December 2022) - Liu, Kui; Loveridge, Fleur A.; Boardman, Richard; Powrie, William
Abstract: Coupled hydrothermal flow can occur in soils, for example in applications such as ground heat storage and nuclear waste disposal. Therefore, approaches to quantitative analysis of water transfer in response to imposed thermal gradients are required, especially in unsaturated conditions. Analysis methods also require validation by laboratory and field data, which can be hard to obtain. This paper explores the possibility of using X-ray μ CT techniques to observe and quantify water content changes in soils under thermal gradients. Specimens of a fine sand and a silty fine sand were prepared at degrees of saturation between 20% and 50%, before being subjected to heating from their base. Repeated scans, set up to balance image quality and scan duration, were carried out during the heating process, and Gaussian decomposition techniques were used to determine the changing soil phase proportions throughout the experiments. Based on these results and the accompanying numerical simulation of the experiments, it is shown that rapid vapour diffusion plays a more significant role than liquid flow in all cases. The rate of water content and hence degree of saturation change was more rapid in the less saturated specimens, especially for the fine sand. In practical terms, these moisture changes would result in reduction in thermal conductivity, especially in the soils of lower saturation. As well as providing insight into the dominant water transfer processes, the experiments show the feasibility of applying X-ray μ CT techniques to thermal problems in soil mechanics. Highlights: Mass transfer due to heating in unsaturated fine soils was observed by X-ray CT. Coarser soil dries more rapidly and to a greater extent than finer soil. Specimens with lower initial saturation experienced the most rapid drying. Simulation confirmed vapour movement to be the main mechanisms of mass transfer. This is encouraged by low water and high vapour permeability respectively.